The Soviet Economy : How it Really Works - Krylov, Constantin A.; Soviet union (Canada : Lexington Books, 1979)
The main goal of this work is not only for the establishment of a new economic system but also a new social order based on that system and why a particular action occurs within the framework of the overall system.
includes index
occ 15/01/2019
Loans
Keywords: Economic history; Russia